2022
DOI: 10.3390/ijerph19138147
|View full text |Cite
|
Sign up to set email alerts
|

Land Fragmentation, Technology Adoption and Chemical Fertilizer Application: Evidence from China

Abstract: Although it has been widely recognized that land fragmentation has increased chemical fertilizer application, little is known about the role of technology adoption in mitigating these adverse effects. To empirically examine the relationship between land fragmentation, technology adoption and chemical fertilizer application, we developed a mediation model. We applied our analysis to a survey data set encompassing 1,388 farm-level samples collected in 14 Chinese provinces in 2019. Our study demonstrated that lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, economies of scale help to achieve increased agricultural productivity and reduce agricultural carbon emissions. In terms of environmental factor inputs, AMS can improve farmers’ expectations of crop yields, which in turn effectively reduces excessive inputs of environmental factors such as pesticides and fertilizers through factor substitution mechanisms [ 45 , 61 ]. Additionally, AMS can help promote the formation of pro-environmental behaviors among farmers, which in turn improves the AGTFP at the micro level [ 44 ].…”
Section: Literature Reviews and Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, economies of scale help to achieve increased agricultural productivity and reduce agricultural carbon emissions. In terms of environmental factor inputs, AMS can improve farmers’ expectations of crop yields, which in turn effectively reduces excessive inputs of environmental factors such as pesticides and fertilizers through factor substitution mechanisms [ 45 , 61 ]. Additionally, AMS can help promote the formation of pro-environmental behaviors among farmers, which in turn improves the AGTFP at the micro level [ 44 ].…”
Section: Literature Reviews and Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies showed that there is a negative or U-shaped correlation between planting size and fertilizer use ( Guo et al, 2022), and that a moderate increase in planting size will increase the FUE (Zhu et al, 2022). Chi et al (2022) believed that the plots fragmentation will lead to more fertilizer inputs, and then lower FUE (Zhu et al, 2022). Besides, the risk attitude of the farmers will affect the fertilizer use and then the FUE.…”
Section: Introductionmentioning
confidence: 98%
“…Behaviour is also in uenced by a combination of other individual characteristics such as literacy, part-time status, access to information, risk perception, social networks 31 and household characteristics 32,33 . Resource endowment constraints 19,[34][35][36] , which are mainly composed of land, labour and capital, are one of the key factors in uencing the technology adoption behaviour of farm households. Smallholder farmers are subject to resource constraints that can be effectively mitigated through agricultural social services 37 and promote farm technology adoption 38 .…”
Section: Introductionmentioning
confidence: 99%